Pupil-directed versus teacher directed classrooms changes in work-study skills at three achievement levels - Young, Donna H. ([Quezon City s.n.], 1973)
The major problem of this study is to determine, compare, and correlate with achievement the changes in work-study skills of children as a group and per achievement level in pupil-directed classrooms and changes in the work-study skills of children as a group and per achievement level in teacher-directed classrooms.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Classroom management; Iowa tests of educational development